2008
DOI: 10.1016/j.expneurol.2008.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAP kinase is involved in central neuropathic pain following spinal cord injury

Abstract: Recent work regarding chronic central neuropathic pain (CNP) following spinal cord injury (SCI) suggests that activation of key signaling molecules such as members of the mitogen activated protein kinase (MAPK) family play a role in the expression of at-level mechanical allodynia. Previously, we have shown that the development of at-level CNP following moderate spinal cord injury is correlated with increased expression of the activated (and thus phosphorylated) forms of the MAPKs extracellular signal related k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 40 publications
(49 reference statements)
3
109
1
2
Order By: Relevance
“…46 Importantly, p38 MAPK modulates neuronal apoptosis following SCI, 47 and elevated levels of spinal p38 have been strongly implicated in the generation and maintenance of neuropathic pain in models of nerve and spinal cord injury. [48][49][50][51] Evidence suggests that these neurotoxic and hyperalgesic effects may result from p38-mediated glial activation and inflammation. 52 Treatment with p38 inhibitors prevents glial proliferation in the spinal cord and decreases the expression of neuropathic pain symptoms after injury.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Importantly, p38 MAPK modulates neuronal apoptosis following SCI, 47 and elevated levels of spinal p38 have been strongly implicated in the generation and maintenance of neuropathic pain in models of nerve and spinal cord injury. [48][49][50][51] Evidence suggests that these neurotoxic and hyperalgesic effects may result from p38-mediated glial activation and inflammation. 52 Treatment with p38 inhibitors prevents glial proliferation in the spinal cord and decreases the expression of neuropathic pain symptoms after injury.…”
Section: Figmentioning
confidence: 99%
“…52 Treatment with p38 inhibitors prevents glial proliferation in the spinal cord and decreases the expression of neuropathic pain symptoms after injury. 39,48,49,51 NorBNI may decrease KOR-mediated p38 signaling, preventing aberrant glial activation. As morphine administration also results in increased expression of many pro-inflammatory cytokines, including interleukin (IL)-1b and IL-6, 2,53-56 using norBNI as an adjuvant may also reduce the development of paradoxical pain observed with prolonged morphine administration.…”
Section: Figmentioning
confidence: 99%
“…p38 MAPK influences the production of proinflammatory cytokines, excitatory molecules, and mediators of oxidative stress (Saklatvala, 2004;Peifer et al, 2006). Previous studies have shown that p38 MAPK is expressed after SCI in microglia/macrophages, neurons and astrocytes, and is implicated in mediating chronic pain (Jin et al, 2003;Crown et al, 2008;Kobayashi et al, 2008). However, p38 MAPK also mediates a variety of cellular functions involved in development, cell survival and proliferation (Roux and Blenis, 2004;Krens et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…예를 들면 below-level pain에는 척수 손상 에 의한 내재성 억제 신경로의 손상이 관여하는 것으로 알려지고 있다 (Gwak et al, 2006). 하지만, 각 부위 척수 후각 신경세포의 과흥분성(hyperexcitability of spinal dorsal horn neurons)은 이들 세 부위에서 유발되는 신경 병증성 통증의 기전에 공통적으로 관여하는 것으로 알려 지고 있다 (Drew et al, 2001;Hains et al, 2003;Crown et al, 2008;Gwak et al, 2008;Carlton et al, 2009). (Hains et al, 2003;Gwak and Hulsebosch, 2005;McAdoo et al, 2005;Waxman, 2006, Liu et al, 2008).…”
unclassified
“…세포내 작용기전 으로서는 cAMP, mitogen-associated protein kinase (MAPK), protein kinase C (PKC), protein kinase A (PKA), cAMP response element binding protein (CREB), calcium/calmodulin-dependent protein kinase (CaMKinase) 등의 활성화에 따른 전사와 번역과정의 활성화로 인한 해 당 단백질의 과발현 및 인산화 등 일련의 분자생물학적 인 반응들이 신경병증성 통증의 유발 및 유지에 관여하 는 것으로 보고되었다 (Crown et al, 2006;Labombarda et al, 2008;Lin et al, 2008 (Hains et al, 2003;Gwak et al, 2003;. 전기생리학적인 연구결과에 의하면, 척수손상 후 척수후각 신경세포들이 비유해성 자극이나 유해성 자극에 의해 과도하게 증가되 고 지속적인 반응을 보이는 것으로 알려지고 있는데 이 러한 상태를 척수후각 신경세포의 과흥분성 또는 중추성 감작이라고 한다 (Hains et al, 2003;Gwak et al, 2006;Crown et al, 2008) (Figure 1 (Chung et al, 1986;Dougherty et al, 199l;Gwak et al, 2008) (Hains et al, 2003;. 만일 WDR 신경세포가 그들의 자극 분별에 관여하는 코드화를 소실한다면 WDR 신경세포의 분포가 감소할 것이나 전기생리학적인 결과로서는 WDR 신경세 포가 증가하였기 때문이다 (Hains et al, 2003;.…”
unclassified